Peran Guru Kelas pada Pelaksanaan Bimbingan dan Konseling dalam Pembentukan Karakter dan Motivasi Berprestasi Siswa di SD Negeri 8 Kranji - Oktrinita Ludwinia Rochmah; Lia Mareza; Aji Heru Muslim (Peneliti.net, 2020)
This research was carried out in Kranji 8 Primary School aimed to find out the role of class teachers in the implementation of guidance and counseling in character building so that students of Kranji 8 Primary School have achievement motivation. Based on observations of researchers at SD Negeri 8 Kranji has several charter and trophies, as in the previous three years starting from 2017-2019. The research will be conducted by researchers using descriptive qualitative research methods. Testing the validity of the data using triangulation. Data collection techniques using observation, interviews, and documents. Triangulation testing used by researchers is by triangulation of sources and triangulation of techniques. The results showed that the teacher at SD Negeri 8 Kranji had done his role in guiding and fostering achievement motivation in students well. The guidance and counseling process carried out by the teacher is done classically, in groups and individually. This can be seen in the achievements that have been obtained by the school during the race. The inhibiting factors for motivation so that students can excel are costs that must be incurred by parents, student motivation is easily decreased and the concentration of students in the process of guidance and counseling that is easily divided so that teacher's advice is sometimes forgotten. The solution that the teacher gives is by giving advice, showing animated videos about motivation, and doing exercises outside of school to open students' insights. Supporting factors for students to have achievement motivation are internal factors in the form of physical factors and psychological factors. Keyword: The teacher's role, Implementation of Guidance and Counseling, Character Building, Achievement Motivation, inhibiting factors and supporting Achievement Motivation